2005
DOI: 10.1039/b415414b
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of nitric oxide on Rh6+ clusters: abundant chemistry and evidence of structural isomers

Abstract: We report the first results of a new instrument for the study of the reactions of naked metal cluster ions using techniques developed by Professor Bondybey to whom this issue is dedicated. Rh6+ ions have been produced using a laser vaporization source and injected into a 3 T Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer where they are exposed to a low pressure (< 10(-8) mbar) of nitric oxide, NO. This system exhibits abundant chemistry, the first stages of which we interpret as involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
133
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 40 publications
9
133
0
2
Order By: Relevance
“…Metal clusters have proven to be useful models for surface and bulk phenomena both in theoretical [9] 1 and experimental [11][12][13][14][15][16] investigations. In particular smaller metal clusters are well suited for quantum mechanical studies, as indicated by the amount of literature available on the subject [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Metal clusters have proven to be useful models for surface and bulk phenomena both in theoretical [9] 1 and experimental [11][12][13][14][15][16] investigations. In particular smaller metal clusters are well suited for quantum mechanical studies, as indicated by the amount of literature available on the subject [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…25 There have also been a few experimental studies of NO adsorption and dissociation on small Rh clusters. In their Fourier transform ion cyclotron resonance studies of reactions of NO with Rh + 6 , Ford et al 30 observed biexponential kinetics, which they have interpreted in terms of structural isomerism. In another experimental study of NO decomposition on small, charged Rh clusters, Anderson et al 31 have reported that, for both cationic and anionic clusters, the reaction rate increases smoothly with cluster size, though the reaction proceeds significantly faster on cationic clusters than on anionic ones.…”
Section: Previous Work On Rhn and No-rhnmentioning
confidence: 99%
“…Their use is advantageous for understanding the behavior of N and O atoms at the atomic and molecular level, since the number of Rh, N, and O atoms involved in the reaction is well defined. [6][7][8][9][10][11] For instance, Mackenzie et al investigated the reduction of NO on rhodium clusters by single collision reactivity experiments performed by Fourier transform mass spectrometry in the gas phase. The experiments suggested that the first NO molecule predominantly adsorbs dissociatively on Rhn + clusters (n < 17).…”
Section: Introductionmentioning
confidence: 99%
“…For Rh6 + , four NO molecules can be reduced yielding N2 before the remaining oxygen atoms disrupt NO reduction; further NO molecules only adsorb onto Rh6O4 + clusters. [6][7][8][9] Harding et al calculated the geometrical structures of stable Rh6O1-4 + clusters and studied the adsorption form of NO on Rh6O4 + using density functional theory (DFT). 12,13 The calculations suggest that stable clusters have an octahedral tetragonal bipyramidal (octahedral) or capped-square pyramidal structure.…”
Section: Introductionmentioning
confidence: 99%